2010
DOI: 10.4097/kjae.2010.59.s.s242
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum and pneumothorax after orthognathic surgery -A case report-

Abstract: The occurrences of pneumomediastinum and pneumothorax after oral and/or maxillofacial surgery are rare, but both are potentially life-threatening complications. Most of the cases that present pneumomediastinum and pneumothorax in the oral and/or maxillofacial surgery result from air dissecting down the fascial planes of the neck. We report a case of a 23-year-old male patient who underwent bilateral sagittal split ramus osteotomy under general anesthesia and developed pneumomediastinum and pneumothorax without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
12
0
4
Order By: Relevance
“…Bimaxillary osteotomy surgery usually performed for facial deformity or cosmetic purpose may have many postoperative functional complications such as bleeding, nerve injury, neuropathic pain, nasal and temporomandibular disorder, and even respiratory insufficiency [ 12 ]. Post-operative aspiration pneumonia due to bleeding and secretion can occur in approximately 0.01–0.06% [ 13 ]. Dyspnea also can develop due to narrowing of the airway from post-operative edematous change or posterior movement of the mandible by bilateral sagittal split ramus osteotomy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bimaxillary osteotomy surgery usually performed for facial deformity or cosmetic purpose may have many postoperative functional complications such as bleeding, nerve injury, neuropathic pain, nasal and temporomandibular disorder, and even respiratory insufficiency [ 12 ]. Post-operative aspiration pneumonia due to bleeding and secretion can occur in approximately 0.01–0.06% [ 13 ]. Dyspnea also can develop due to narrowing of the airway from post-operative edematous change or posterior movement of the mandible by bilateral sagittal split ramus osteotomy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, excessive pressure in the right upper lobe despite normal respiratory tidal volume is believed to have triggered the right upper lobe parenchyma tearing and bronchus dissection, leading to pneumomediastinum and right pneumothorax. 20 Edwards et al described a case series of two patients who developed pneumomediastinum and right pneumothorax postoperatively after orthognathic surgery. In their first patient, introduction of mediastinal and pleural air was probably secondary to increased intra-alveolar pressure from mucous plugs plus vigorous ventilation with an Ambu-bag.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumomediastium has been noted following orthognatic surgery [4], tonsillectomy [5], vesico-urethral reimplantation operation [6]. Subcutaneous and intermuscular emphysema, and pneumomediastinum following arthroscopic shoulder surgery have rarely been reported [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The recent trend for arthroscopic shoulder surgery is the sitting position for good visualization of operating fields; therefore the relationship of pneumomediastinum to the position may be a serious problem. But, other articles reported that pneumomediastinum has been developed with other positions [4-6]. Therefore, operative position is less associated with pneumomediastinum.…”
Section: Discussionmentioning
confidence: 99%